Early diagnosis of external ventricular drainage infection: results of a prospective study. Issue 7 (1st July 2003) - Pfisterer, W; Mühlbauer, M; Czech, T; Reinprecht, A
Abstract : Objectives: The aim of this study was to evaluate the influence of total drainage time on the risk of catheter infection, and the predictive value of standard laboratory examinations for the diagnosis of bacteriologically recorded cerebrospinal fluid (CSF) infection during external ventricular drainage. Methods: During a three year period, all patients of the neurosurgical intensive care unit (ICU), who received an external ventricular drain, were prospectivly studied. Daily CSF samples were obtained and examined for cell count, glucose and protein content. Bacteriological cultures were taken three times a week, and serum sepsis parameters were determined. Results: 130 patients received a total of 186 external ventricular drains. The ventricular catheters were in place from one to 25 days (mean 7.1 days). In 1343 days of drainage, the authors recorded 41 positive bacteriological cultures in 21 patients between the first and the 22nd drainage day (mean 6.4). No significant correlation was found between drainage time and positive CSF culture. The only parameter that significantly correlated with the occurrence of a positive CSF culture was the CSF cell count (unpaired t test, p<0.05). Conclusions: Drainage time is not a significant risk factor for catheter infection. Increasing CSF cell count should lead to the suspicion of bacteriological drainage contamination. Other standard laboratory parameters, such as peripheral leucocyte count, CSF glucose, CSF protein, or serum sepsis parameters, are not reliable predictors for incipient ventricular catheter infection.